Effects of Two Culture Modes on Muscular Nutrition Content and Volatile Flavor in Chinese Longsnout Catfish (Leiocassis longirostris) - Luo Zhou; Yingbing Su; Daiqin Yang; Qiong Shi; Tilin Yi; Zhengyong Wen (Biology, 2025)
Thus far, various aquaculture modes have been developed to facilitate the rapid growth of the aquaculture industry and thus meet the heavy demand for aquatic products for human consumption. However, the effects of different culture modes on fish muscular nutritional content and volatile flavor are rarely reported. In the present study, we evaluated the differences in muscular nutrition content and dietary flavor between Chinese longsnout catfish (Leiocassis longirostris) groups cultured in two different modes, i.e., flow-through water tanks (CWWL) and traditional ponds (CWWC). Our statistical results showed that a significantly higher crude protein content and lower crude fat levels were observed in the CWWL group than in the CWWC group (p < 0.05). Similarly, the contents of total aromatic amino acids (Total ∑TAA) and total dicarboxylic amino acids (Total ∑DAA) were also significantly higher in the CWWL group. Among the fatty acids, long-chain polyunsaturated fatty acids (LC-PUFAs), including eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), and arachidonic acid (ARA), were recorded at 1.44%, 2.5%, and 9.09%, respectively, in the CWWL group, which were dramatically higher than in the CWWC group. Conversely, the contents of volatile compounds, including 2-tridecanone, dimethyl trisulfide, and isophorone, in the CWWC group were also significant higher, which, however, may contribute to an unpleasant sensory experience. Conversely, other compounds like 2-methylbutanal and 2,3-butanedione were prevalent in the CWWL group, which can induce rich nutty and buttery flavors and thus enhance the freshness of flavor profiles. In conclusion, Chinese longsnout catfish cultured in flow-through tanks show higher nutritional value and better sensory flavor in comparison with those raised in ponds. These findings not only provide novel insights into the potential effects of aquaculture modes on muscular nutrition content and dietary flavor for Chinese longsnout catfish but also lay a solid foundation for optimizing practical culture modes to improve the global aquaculture industry.